Public Speaking: Finding Your Voice, Global Edition - Michael, Osborn (Pearson, 2015)
This top-selling, comprehensive introductory public speaking title highlights and develops the theme of “Finding Your Voice.” It helps students develop as speakers and as people, as they gain presentation skills and confidence, discover causes that interest and engage them, and give them a sense of purpose. This theme reinforces the book’s primary goal of helping students to become better communicators in their classrooms, workplaces and communities.